“These things happen”: Hashtag activism and sexual harassment in the South African film and television industries - Paleker, Gairoonisa (Agenda, 2020)
In August 2017, the South African advocacy group Sisters Working in Film and Television (SWIFT) launched the #ThatsNotOk campaign, which has to date produced six episodes of short films (one episode in two parts, making it seven in total) elucidating the different forms sexual harassment takes, and the different scenarios in which it occurs, in the South African film and television industries. This profile engages with SWIFT and the Public Service Announcement (PSA) films as discursive sites and texts respectively, and provides textual analyses of the PSAs in the context of digital feminism and feminist activism against sexual harassment in the film and television industries. The profile motivates that as expressions of digital feminism, the PSAs critique the pervasiveness and normalisation of sexual harassment, while failing to engage with or critique the neoliberal logic and structure of the film and television industries.
Keywords: #ThatsNotOk; Irina; South African film and television; digital feminism; hashtag activism